Comparative Home Country Influences on Management Practices Abroad - Daniels, John D.; Arpan, Jeffrey S. (Academy of Management Journal, 1972)
International firms from different countries exhibit distinct geographic expansion and ownership preferences. The subsidiary operations in the United States also reflect differences by parent nationality regarding the location of control of financial decisions as well as the relative importance of internal and external variables in the formulation of financial control policies.